ANALYSIS FEASIBILITY OF DAIRY BUFFALO MILK BUSINESS SYARIAH IN LUBUK PAKAM DISTRICT, DELI SERDANG REGENCY - Putra, Yudha Andriansyah; Harahap, Mailina; Siregar, Gustina; Sitorus, Yuda (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine and analyze the feasibility of a dairy buffalo business in syariah system in Lubuk Pakam District, Deli Serdang Regency.This research was conducted in Lubuk Pakam District, Deli Serdang Regency. This study used a saturated or census sampling method. In this study, the respondents were 7 dairy buffalo milk farmers in Lubuk Pakam District. Data analysis uses BEP (Break Event Point) and R/C ratio (Return Cost Ratio). The results of the feasible to cultivate because it had obtained the R/C ratio (Revenue Cost Ratio) is 2.51 1 and the total production ("3,476 liters") production BEP (107.03 liters) means that the dairy buffalo business in Lubuk Pakam District, Deli Serdang Regency is profitable. Operational Aspects Product Quality, The recommended location for the cage, Number of Workers and Wages. Marketing Aspect that become attention from this research are Consumer Interest Analysis, Market Position Apart from being feasible from the results of this research, this buffalo milk business is sharia provisions and has sustainability for running the business in the future.